The Bible now [homosexuality, abortion, women, death penalty, earth] - Friedman, Richard Elliott 1946-; Dolansky, Shawna (New York Oxford University Press, 2011)
For millennia, people have used the Bible as a touchstone on important social and political questions, and rightly so. But many use the Bible simply as a weapon to wield against opponents in a variety of debates--without knowing what the Bible actually says about the issue in question. In The Bible Now, two respected biblical scholars, Richard Elliott Friedman and Shawna Dolansky, tell us carefully what the Hebrew Bible says or does not say about a wide range of issues--including homosexuality, abortion, women's status, capital punishment, and the environment. In fascinating passages that shed
Cover; Contents; Preface; ONE: Homosexuality; TWO: Abortion; THREE: Women's Status; FOUR: Capital Punishment; FIVE: The Earth; Afterword; Notes; Subject Index; Scripture Index
Includes bibliographical references and indexes
Electronic reproduction; Available via World Wide Web
Online-Ausg.
Keywords: Bible -- Criticism, interpretation, etc; Ethical problems; Ethics in the Bible; Bible ; O.T ; Criticism, interpretation, etc; Electronic books